The role of hormonal factors and endocrine therapy in ovarian cancer - Serkies, Krystyna; Sinacki, Marcin; Jassem, Jacek (Contemporary Oncology/Współczesna Onkologia, 2013)
The efficacy of the second-line chemotherapy commonly used in both relapsed ovarian cancer patients and those with primary treatment failure remains unsatisfactory. This therapy has a small effect on survival, whereas associated toxicity may diminish the patient’s quality of life. Hormonal factors play a role in ovarian tumorigenesis, and inhibition of the stimulating effects of estrogens may exert a clinical benefit. The role of hormonal therapy as a palliative therapeutic alternative for ovarian cancer remains undetermined. This modality may result in long-term stabilization of disease in individual patients and less frequently in tumor remission. In this article the role of hormonal factors and recent literature of various forms of hormonal therapy for ovarian cancer are presented.